2015
DOI: 10.3402/polar.v34.25582
|View full text |Cite
|
Sign up to set email alerts
|

Multi-frequency observations of seawater carbonate chemistry on the central coast of the western Antarctic Peninsula

Abstract: Assessments of benthic coastal seawater carbonate chemistry in Antarctica are sparse. The studies have generally been short in duration, during the austral spring/summer, under sea ice, or offshore in ice-free water. Herein we present multi-frequency measurements for seawater collected from the shallow coastal benthos on a weekly schedule over one year (May 2012ÁMay 2013), daily schedule over three months (MarchÁMay 2013) and semidiurnal schedule over five weeks (MarchÁApril 2013). A notable pH increase (max p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…; Smale & Barnes, ). Predictions also suggest that other parameters of importance for marine life, such as chlorophyll a concentrations, should significantly vary in the future (Schram, Schoenrock, McClintock, Amsler, & Angus, 2015a,b; Turner et al., ). Based on the available abiotic and biotic data, the present results suggest that the impact of these future changes on benthic organisms will have no equivalent in comparison with what happened in the past century.…”
Section: Discussionmentioning
confidence: 99%
“…; Smale & Barnes, ). Predictions also suggest that other parameters of importance for marine life, such as chlorophyll a concentrations, should significantly vary in the future (Schram, Schoenrock, McClintock, Amsler, & Angus, 2015a,b; Turner et al., ). Based on the available abiotic and biotic data, the present results suggest that the impact of these future changes on benthic organisms will have no equivalent in comparison with what happened in the past century.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, low pH had a positive effect on size of O. validus , consistent with previous observations on the species (Gonzalez‐Bernat et al ., ). The robustness in O. validus may be related to the seasonally low ambient pH that the species' larvae experience during the winter spawning season across much of Antarctica (Kapsenberg et al ., ; Schram et al ., ). For example, in McMurdo Sound, where our animals were collected, Kapsenberg et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in McMurdo Sound, where our animals were collected, Kapsenberg et al (2015) reported average seawater pH as low as pH (T) 7.93 to 7.94 during May and June. O. validus populations on coastal Antarctic Peninsula also likely experience low pH levels during winter spawning, with Schram et al (2015) reporting pH during winter months of pH (T) 8.0. This response, however, was not observed in S. neumayeri, which spawns in spring when pH levels increase, and has been measured at pH (T) 8.24 in McMurdo Sound (McNeil et al, 2010;Kapsenberg et al, 2015) and pH as high as pH (T) 8.62 along the Antarctic Peninsula (Schram et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Ambient temperature and pH levels (1.5°C and pH 8.0) were selected based on annual ambient seawater temperature and pH conditions measured at Palmer Station on the WAP (Schram et al 2015b). Near-future temperature and pH levels were selected based on estimates predicted to occur by 2100 (IPCC 2013).…”
Section: Methodsmentioning
confidence: 99%